Coronary risk factors associated with OCT macrophage images and their response after CoCr everolimus-eluting stent implantation in patients with stable coronary artery disease. (October 2017) - Taguchi, Yuya; Itoh, Tomonori; Oda, Hideto; Uchimura, Yohei; Kaneko, Kyosuke; Sakamoto, Tsubasa; Goto, Iwao; Sakuma, Masafumi; Ishida, Masaru; Terashita, Daisuke; Otake, Hiromasa; Morino, Yoshihiro; et al.
Abstract: Background and aims: The aim of this study was to evaluate the accumulation of optical coherence tomography (OCT)-macrophages and OCT findings after CoCr everolimus-eluting stent placement, in addition to coronary risk factors. Methods: A total of 89 lesions in 89 patients were registered in the 1- and 3-month cohort of the multi-centre study. Lesion characteristics and post-procedure OCT images were evaluated immediately and 1 and 3 months after stenting. Patients were divided into low and high macrophage grade groups based on the median macrophage grade. Results: Low-density lipoprotein cholesterol (LDL-C) levels, the prevalence of diabetes mellitus, HbA1c and blood glucose levels in the high macrophage grade group were significantly higher than in the low macrophage grade group ( p  = 0.025, p  = 0.040, p  = 0.032, and p  = 0.010). Moreover, total lipid arc and length and number of thin-cap fibroatheromas (TCFAs) in the high macrophage grade group were significantly higher than in the low macrophage group ( p  = 0.008, p  = 0.002, and p  = 0.012). After CoCr everolimus-eluting stenting, there was a trend towards a greater number, height, and area of irregular protrusions in the high macrophage grade group compared to the low macrophage grade group ( p  = 0.091, p  = 0.059, and p  = 0.085). Multivariate logistic regression analysis showed that diabetes mellitus was a significant predictor of high macrophage grades (odds ratio: 2.8, 95% CI: 1.1–7.3, p  = 0.030). Conclusions: The accumulation of OCT-macrophages was associated with diabetes mellitus in patients with coronary artery disease. Moreover, macrophage accumulation and diabetes mellitus may be associated with irregular protrusions just after stenting. Highlights: This manuscript evaluated the relationship between OCT-macrophage and coronary risk factors. Diabetes mellitus was a significant predictor of high macrophage grades. OCT-macrophage may be associated with irregular protrusions just after stenting.